Self-stigma and antiretroviral therapy adherence among people living with HIV/AIDS: A cross-sectional study - Chinedu Okafor; Amina Bello (Science Center Group, 2026)
Background: Health-seeking behavior remains a critical determinant of health outcomes in coastal Self-stigma remains a critical psychosocial challenge among people living with HIV/AIDS and may interfere with long-term engagement in antiretroviral therapy. Internalized shame, fear of disclosure, and negative self-perception can disrupt medication-taking routines and reduce adherence, particularly in settings where HIV-related stigma remains socially embedded. Objective: This study aimed to examine the association between self-stigma and antiretroviral therapy adherence among people living with HIV/AIDS attending a Nigerian antiretroviral therapy clinic. Methods: This analytical cross-sectional study was conducted among 87 adults receiving antiretroviral therapy at a single HIV clinic. Consecutive sampling was used to recruit eligible respondents during the data collection period. Self-stigma was measured using the Internalized AIDS-Related Stigma Scale, while adherence was assessed using the AIDS Clinical Trials Group Adherence Questionnaire. Data were analyzed using descriptive statistics, Fisher’s exact test, independent samples t-test, Spearman’s rank correlation, and multivariable logistic regression. Statistical significance was set at p < 0.05. Results: Respondents with suboptimal adherence had significantly higher self-stigma scores than those with optimal adherence (18.8 ± 3.6 vs. 13.7 ± 4.0; p < 0.001). Self-stigma showed a moderate negative correlation with adherence percentage (r = -0.49; p < 0.001). Multivariable logistic regression showed that moderate self-stigma (AOR = 0.39; 95% CI: 0.13–0.92; p = 0.034) and high self-stigma (AOR = 0.16; 95% CI: 0.04–0.59; p = 0.006) were independently associated with lower odds of optimal adherence. Conclusion: Self-stigma was significantly associated with poorer antiretroviral therapy adherence among people living with HIV/AIDS in this Nigerian ART clinic. The findings should be interpreted cautiously because of the cross-sectional design, single-clinic setting, and modest sample size. HIV care services should integrate stigma-sensitive adherence counseling, safe disclosure support, family-based support, and clinic retention strategies into routine treatment programs.